Learning disability nurse provision in children's hospitals: hospital staff perceptions of whether it makes a difference - Kate Oulton; Jo Wray; Angela Hassiotis; Charlotte Kenten; Jessica Russell; Irene Tuffrey-Wijne; Mark Whiting; Faith Gibson (BMC, 2019)
Abstract Background In response to multiple United Kingdom investigations and inquiries into the care of adults with learning disabilities, Mencap produced the Getting it Right Charter which campaigned for the appointment of a Learning Disability Liaison Nurse in every hospital. More recent best practice guidelines from the Care Quality Commission included the need for all children's units to have access to a senior learning disability nurse who can support staff and help them manage difficult situations. However, little evidence exists of the extent of learning disability nurse provision in children's hospitals or the nature and impact of this role. Here we report selected findings from a national mixed methods study of hospital care for children and young people with and without learning disabilities in England. The extent of learning disability nurse provision in children's hospitals is described and perceptions of staff working in hospitals with and without such provision is compared. Methods Semi-structured interviews were conducted with senior staff across 15 children's hospitals and an anonymous survey was sent to clinical and non-clinical staff with patient (children and young people) contact within these hospitals. The survey focused on six different elements of care for those with and without learning disability, with additional questions concerning identifying and tracking those with learning disabilities and two open-ended questions. Results Forty-eight senior staff took part in interviews, which included a subset of nine nurses and one allied health professional employed in a dedicted learning disability nurse role, or similar. Surveys were completed by 1681, of whom 752 worked in a hospital with dedicated learning disability nurse provision. We found evidence of limited and varied learning disability nurse provision which was valued by hospital staff and shown to positively impact their perceptions of being capable to care for children and young people with learning disabilities, but not shown to increase staff perceptions of capacity or confidence, or how children and young people are valued within the hospital, their safety or access to appointments. Conclusion Further consideration must be given to how learning disability nurse roles within children's hospitals are best operationalised in practice to have the greatest impact on staff and families, as well as how we monitor and evaluate them to ensure they are being utilised effectively and efficiently. Trial registration The study has been registered on the NIHR CRN portfolio 20,461 (Phase 1), 31,336 (Phases 2-4).